Clinical application of sequencing-based methods for parallel preimplantation genetic testing for mitochondrial DNA disease and aneuploidy - Spath, K; Babariya, D; Konstantinidis, M; Lowndes, J; Child, T; Grifo, JA; Poulton, J; Wells, D (Elsevier, 2021)
Objective To validate and apply a strategy permitting parallel preimplantation genetic testing (PGT) for mitochondrial DNA (mtDNA) disease and aneuploidy (PGT-A). Design Preclinical test validation and case reports. Setting Fertility centers. Diagnostics laboratory. Patients Four patients at risk of transmitting mtDNA disease caused by m.8993T>G (Patients A and B), m.10191T>G (Patient C), and m.3243A>G (Patient D). Patients A, B, and C had affected children. Patients A and D displayed somatic heteroplasmy for mtDNA mutations. Interventions Embryo biopsy, genetic testing, and uterine transfer of embryos predicted to be euploid and mutation-free. Main Outcome Measures Test accuracy, treatment outcomes, and mutation segregation. Results Accuracy of mtDNA mutation quantification was confirmed. The test was compatible with PGT-A, and half of the embryos tested were shown to be aneuploid (16/33). Mutations were detected in approximately 40% of embryo biopsies from Patients A and D (10/24) but in none from Patients B and C (n = 29). Patients B and C had healthy children following PGT and natural conception, respectively. The m.8993T>G mutation displayed skewed segregation, whereas m.3243A>G mutation levels were relatively low and potentially impacted embryo development. Conclusions Considering the high aneuploidy rate, strategies providing a combination of PGT for mtDNA disease and aneuploidy may be advantageous compared with approaches that consider only mtDNA. Heteroplasmic women had a higher incidence of affected embryos than those with undetectable somatic mutant mtDNA but were still able to produce mutation-free embryos. While not conclusive, the results are consistent with the existence of mutation-specific segregation mechanisms occurring during oogenesis and possibly embryogenesis.